# L76 - Spring 2006 Math 308-505 7 Laplace Transforms 7.6...

This preview shows pages 1–3. Sign up to view the full content.

Spring 2006 Math 308-505 7 Laplace Transforms 7.6 Transforms of Discontinuous and Periodic Functions Fri, 03/Mar c ± 2006, Art Belmonte Summary Heaviside function The Heaviside unit step function is a piecewise continuous function deﬁned by u ( t ) = ± 0 , for t < 0 ; 1 , for t 0 . For c R (typically c > 0), the translate of u is deﬁned by u c ( t ) = u ( t - c ) = ± 0 , for t < c ; 1 , for t c . The interval function is deﬁned by u ab ( t ) = u ( t - a ) - u ( t - b ) = 0 , for t < a ; 1 , for a t < b ; 0 , for t b . The Heaviside function is easy to implement numerically in MATLAB in a vectorized fashion. To learn all about it, read Chapter 6 (“Advanced use of dﬁeld7”) in your lab manual! Also read about Polking’s sqw square wave function M-ﬁle. (It’s available to you on CalcLab and is easily transferred to your Windows XP LABS account or home.) Finally, study the MATLAB Examples in this lecture handout. Even better, as of Fall 2003 I have learned how to fully implement the Heaviside function in a symbolic fashion for both Laplace transform and graphing purposes. Accordingly, your work will be much easier than the folks had it in the Spring! Periodic Functions If f ( t + T ) = f ( t ) for all t ,then f is periodic with period T (or T -periodic). Its window is deﬁned as f T ( t ) = ± f ( t ), 0 t < T ; 0 , t T . More Laplace transforms In the following, a , b , c are constants, p is a nonnegative constant, L { f ( t ) } = F ( s ) is the Laplace transform of f , and the Laplace transform of the window g T of the piecewise continuous T -periodic function g is given by L { g T ( t ) } = G T ( s ) . L { u ( t - c ) } = e - cs s L { u ( t ) } = e - as - e - bs s L { f ( t - p ) u ( t - p ) } = e - ps F ( s ) L { f ( t ) u ( t - p ) } = e - ps L { f ( t + p ) } ( s ) L { g ( t ) } = G T ( s ) 1 - e - sT = ² T 0 g ( t ) e - st dt 1 - e - Hand Examples Example A Find the Laplace transform of e 2 ( t - 1 ) u ( t - 1 ) . Solution Let f ( t ) = e 2 t .Then F ( s ) = L { f ( t ) }= 1 s - 2 . Therefore L ³ e 2 ( t - 1 ) u ( t - 1 ) ´ = L { f ( t - 1 ) u ( t - 1 ) } = e - s F ( s ) = e - s s - 2 . Example B Compute the Laplace transform of e - t u ( t - 1 ) . Solution Since L { u ( t - 1 ) } = e - s s ,wehave L µ e - t u ( t - 1 ) = e - ( s + 1 ) s + 1 . Example C Determine the Laplace transform of u ( t - π 2 ) cos 3 t . Solution We have cos ( 3 ( t + π 2 )) = cos ( 3 t + 3 2 π) = sin 3 t via trig. So L µ u ( t - π 2 ) cos 3 t = e - π 2 s L µ cos ( 3 ( t + π 2 )) = 3 e - π 2 s s 2 + 9 . Example D Let f ( t ) = 0 , t < 0 t , 0 t < 3 3 , t 3 .Deﬁne f in terms of the Heaviside function, then compute its Laplace transform. Solution f ( t ) = t ( u ( t ) - u ( t - 3 )) + 3 u ( t - 3 ) = tu ( t ) - ( t - 3 ) u ( t - 3 ) implies L { f ( t ) } = e - 0 s s 2 - e - 3 s s 2 = 1 - e - 3 s s 2 . 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Example E Find the inverse Laplace transform of e - 2 s s + 3 . Solution Let F ( s ) = 1 s + 3 .Then f ( t ) = L - 1 { F ( s ) }= e - 3 t . Thus L - 1 ± e - 2 s 1 s + 3 ² = u ( t - 2 ) f ( t - 2 ) = u ( t - 2 ) e - 3 ( t - 2 ) = ± 0 , t < 2 ; e - 3 ( t - 2 ) , t 2 .
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 6

L76 - Spring 2006 Math 308-505 7 Laplace Transforms 7.6...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online